Bimetallic nano alloy architecture on a special polymer: Ni or Cu merged with Pd for the promotion of the Mizoroki-Heck reaction and the Suzuki-Miyaura coupling - Patil, Vijay P.; Kashid, Abhijit A.; Solanki, Bhanupratap S.; Kharul, Ulhas K.; Iyer, Suresh (Journal of Chemical Sciences, 2021)
Novel Ni-Pd and Cu-Pd bimetallic nano alloys was designed and heterogenized on the highly robust ABPBI [poly(2,5-benzimidazole)] polymer in high yields using NaBH4 as reducing agent. These were versatile ligand free catalysts for the Mizoroki-Heck reaction and Suzuki-Miyaura coupling. The bimetallic Ni-Pd-ABPBI catalyst for the Mizoroki-Heck reaction of 4-iodo anisole could be recycled 5 times with high yields. Aryl bromides could also be activated for the Mizoroki-Heck reaction using Cu-Pd-ABPBI NP catalysts, with moderate yields. Graphic abstractSynopsis Novel bimetallic Ni-Pd and Cu-Pd nano alloys, heterogenized on the robust ABPBI [poly(2,5-benzimidazole)] polymer using NaBH4 as reducing agent, is described. These were versatile ligand free, noble metal conservative catalysts, for the Mizoroki-Heck reaction and the Suzuki-Miyaura coupling. Aryl bromides were activated for the Mizoroki-Heck reaction using the Cu-Pd-ABPBI catalyst.
Keywords: Bimetallic nano alloys; Cu-Pd-ABPBI; Mizoroki-Heck reaction; Ni-Pd-ABPBI; Suzuki coupling

Bimetallic Ni-Pd synergism-mixed metal catalysis of the mizoroki-heck reaction and the suzuki-miyaura coupling of aryl bromides - Kashid, Abhijit A.; Patil, Dharmaraj J.; Mali, Ramling D.; Patil, Vijay P.; Neethu, T. V.; Meroliya, Heena K.; Waghmode, Shobha A.; Iyer, Suresh (Catalysis Letters, 2021)
A combination of Pd and Ni complexes activated aryl bromides for the thermal Mizoroki-Heck reaction and Suzuki coupling giving high yields in short reaction times. A thermal redox mechanism probably occurs whereby Ni complex transfers electron and reduces the Pd (II) to Pd (0) which then takes the reactants through the standard protocol of oxidative-addition, migratory insertion and reductive elimination, typical for the Mizoroki-Heck reaction and the Suzuki coupling. [GRAPHICS] .
Keywords: Bimetallic catalysis; Mizoroki-Heck; Nickel complexes; Pd(OAc)2; Suzuki coupling

Bimetallic Ni–Pd synergism—mixed metal catalysis of the mizoroki-heck reaction and the suzuki–miyaura coupling of aryl bromides - Kashid, Abhijit A.; Patil, Dharmaraj J.; Mali, Ramling D.; Patil, Vijay P.; Neethu, T. V.; Meroliya, Heena K.; Waghmode, Shobha A.; Iyer, Suresh (Catalysis Letters, 2021)
A combination of Pd and Ni complexes activated aryl bromides for the thermal Mizoroki-Heck reaction and Suzuki coupling giving high yields in short reaction times. A thermal redox mechanism probably occurs whereby Ni complex transfers electron and reduces the Pd (II) to Pd (0) which then takes the reactants through the standard protocol of oxidative-addition, migratory insertion and reductive elimination, typical for the Mizoroki-Heck reaction and the Suzuki coupling.